The Influence of Parents on Child Development: The Foundations of Character Building - Wijaya, Gatra (Lembaga Bale Literasi, 2024)
This study explores the impact of the role of parents on child development in various aspects. Using a combination of surveys and interviews, we analyze parenting, family communication, and the level of parental involvement in children's lives. The findings suggest that positive interactions and supportive parenting have a significant impact on a child's well-being, while a lack of attention or an authoritarian approach can negatively influence parental influence on children and the relationship between parenting and child development. This study explores the various factors that influence parenting and their implications for child development. The research methods used are literature study and secondary data analysis. The results showed that positive parenting has a significant influence on children's development in the cognitive, social, and emotional fields. In addition, this study also found that good communication between parents and children and the quality of family relationships also have a positive impact on child development. The implications of this study can be used as a guideline for parents in supporting optimal development of children through loving and understanding parenting.